A Prospective Study to Evaluate the Impact of Golimumab Therapy on Work Productivity and Activity, and Quality of Life in Patients With Rheumatoid Arthritis, Psoriasis Arthritis and Axial Spondyloarthritis in a Real Life Setting in AUSTRIA. The GO-ACTIVE Study - Dejaco, Christian; Mueller, Thomas; Zamani, Omid; Kurtz, Ulrike; Egger, Stefan; Resch-Passini, Johannes; Totzauer, Anna; Yazdani-Biuki, Babak; Schwingenschloegl, Thomas; Peichl, Peter; Kraus, Angelika; Naerr, Gerhard W. (Frontiers in Medicine, 2022)
Objective To analyze real-world evidence on work productivity and daily activity impairment (WPAI) and health-related quality of life (HRQoL) in rheumatoid arthritis (RA), psoriatic arthritis (PsA), and axial spondyloarthritis (axSpA) patients treated with golimumab in Austria. Methods This was a prospective, non-interventional, multi-center study conducted in RA, PsA and axSpA patients initiating golimumab between April 2016 and May 2020 in 40 centers in Austria. WPAI, HRQoL (RAQoL, ankylosing spondylitis (AS)QoL and PsAQoL) questionnaires and disease activity (Clinical Disease Activity Index, CDAI, in RA and PsA; Bath Ankylosing Spondylitis Disease Activity Index, BASDAI, in axSpA) were assessed at baseline and months 3, 6, 12, 18, and 24. Association between WPAI and disease activity was tested using linear regression. Results We enrolled 233 patients (RA, n = 95; axSpA, n = 69; PsA, n = 69), 110 patients were followed up to month 24. Mean age was 50.2 ± 14.2 years; 64% were female. Disease activity decreased from baseline to month 24 (RA: CDAI −24.3 ± 13.5; axSpA: BASDAI −4.4 ± 2.1, and PsA: CDAI −21.7 ± 8.5, p < 0.0001, each). Total work productivity impairment (TWPI), activity impairment and presenteeism subscores continuously decreased throughout month 24 in all indications: RA (−58.3 ± 23%, −62.6 ± 23.8% and −61.7 ± 23.3%, respectively as compared to baseline; p < 0.0001, each), axSpA (−34.4 ± 38.3%, p = 0.0117; −60.9 ± 25.9%, and −43.8 ± 26.6%, respectively, p ≤ 0.0001 both) and PsA (−35.8 ± 43.7%, p = 0.0186; −52.3 ± 25.4%, p < 0.0001; and −43.3 ± 33.5%, p = 0.0007, respectively). Absenteeism scores decreased only in RA patients (−9.2 ± 24.9%, p = 0.0234). HRQoL improved between baseline and month 24 (RAQoL: −12.6 ± 7.5; ASQoL: −8.0 ± 4.3; PsAQoL; −8.3 ± 6.4, p < 0.0001, each). TWPI, presenteeism and activity impairment strongly associated with disease activity throughout the study. Conclusions This real-world study confirms the benefit of golimumab on work productivity/daily activity impairment in Austrian RA, PsA, and axSpA patients.